Differential associations between television viewing, computer use, and adiposity by age, gender, and race/ethnicity in United States youth: A cross‐sectional NHANES analysis. - Zink, Jennifer; Liu, Benmei; Yang, Chih‐Hsiang; Herrick, Kirsten A.; Berrigan, David (Pediatric Obesity, 2023)
Summary: Background: Time spent on screens and adiposity change rapidly from childhood to adolescence, with differences by gender and race/ethnicity. Objective: Apply time‐varying effect models (TVEMs) to a nationally representative sample of youth to identify the age ranges when the cross‐sectional associations between television viewing, computer use, and adiposity are significant. Methods: Data from 8 to 15‐year‐olds (n = 3593) from the National Health and Nutrition Examination Survey (2011–2018) were extracted. TVEMs estimated the associations between television viewing, computer use, and fat mass index as dynamic functions of the participants' age, stratified by gender and race/ethnicity. Results: TVEMs revealed age‐specific statistically significant associations that differed by gender and race/ethnicity. Notably, computer use was related to higher adiposity in non‐Hispanic White females aged 9.3–11.4 years (slope β‐range: 0.1–0.2) and in non‐Hispanic Black females older than 14.8 years (β‐range: 0.1–0.5). In males, these age windows were 13.5–15.0 years (non‐Hispanic White, β‐range: 0.1–0.2), 11.4–13.0 years (non‐Hispanic Black, β‐range: 0.1–0.14), and older than 13.0 years (Hispanic, β‐range: 0.1–0.4). Conclusions: More research during the specific age ranges in the demographic subgroups identified here could increase our understanding of tailored interventions in youth.